Legal Analysis of Transnational Crimes in the Scope of Tax Crimes in View of International Law Words - Alghazali, Muhammad Syammakh Daffa; Daulay, Zainul; Sofyan, Syofirman (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2023)
In order to achieve the ideals of the Unitary State of the Republic of Indonesia, which will bring prosperity to its people, resilience in the economic sector plays a significant role. However, the circulation of black money still haunts Indonesia in realizing its goals. One practice that is detrimental to the State of Indonesia is tax evasion. Although Indonesia already has several regulations regarding preventing and eradicating money laundering crimes. However, it is still difficult to prosecute the perpetrators of these crimes. Therefore, this research focuses on the regulation of Indonesian law regarding transnational crimes within the scope of financial transactions resulting from criminal acts in the field of taxation. Second, Indonesian law enforcement acts against transnational crimes within the scope of financial transactions resulting from criminal acts in the field of taxation. The focus of the study uses normative research methods with a juridical-qualitative analysis method. The results of this study conclude that even though Indonesia already has legal instruments related to the prevention and eradication of money laundering, especially the proceeds of crime in the field of taxation, there is a legal loophole in the regulation of Special Purpose Vehicles (SPV) so that it is necessary to reorganize SPV arrangements so that they no longer become loopholes for criminals and strengthen the FIU in terms of law enforcement.